The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.annepidem.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of maternal prenatal weight and offspring cardiometabolic health in midchildhood

Abstract: Purpose To examine the relations of maternal pre-pregnancy body mass index (ppBMI) and gestational weight gain (GWG) with offspring cardiometabolic health. Design We studied 1,090 mother-child pairs in Project Viva, a Boston-area pre-birth cohort. We measured overall (DXA total fat; BMI z-score) and central adiposity (DXA trunk fat), and SBP in offspring at 6–10 years. Fasting bloods (n=687) were assayed for insulin and glucose (for calculation of HOMA-IR), triglycerides, leptin, adiponectin, hsCRP and IL-6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 33 publications
5
96
2
2
Order By: Relevance
“…Among the 20 articles that met the inclusion criteria, six included both exposures 6,27,28,29,30,31 . The average score of the selected articles was 15.4, with a minimum of 13 and a maximum of 18.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 20 articles that met the inclusion criteria, six included both exposures 6,27,28,29,30,31 . The average score of the selected articles was 15.4, with a minimum of 13 and a maximum of 18.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies were conducted in the United States 5,6,29,30,32,33,34,35,36,37 , two in the United Kingdom 28,38 , two in Denmark 32,39 , one in Australia 27 , one in Brazil 31 , and one in Portugal 40 ( Table 1). The number of participants in the cohorts ranged from 78 34 to 3,263 38 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Project Viva, which recruited 1,090 mother-child pairs, demonstrated that each 5-unit increase in maternal BMI pre-pregnancy was associated with a 0.92 kg increase in total fat and 0.39 kg trunk fat in the offspring at birth. Each 5 kg of weight gained during pregnancy was positively and significantly associated with greater total and trunk adiposity (determined using dual x-ray absorptiometry) in the offspring, after adjustment [64]. Whilst mothers with gestational diabetes and pre-pregnancy obesity are…”
Section: The Importance Of Maternal Health In Relation To the Growthmentioning
confidence: 99%
“…15 Maternal prepregnancy obesity has been linked to higher offspring systolic blood pressure (SBP), likely through intrauterine mechanisms. 16,17 In animal and human studies, maternal obesity also has been associated with high blood Hcy levels. 18,19 From this perspective, studying the association between maternal Hcy and child BP in the presence and absence of maternal prepregnancy obesity could provide new insight into their joint association with child BP.…”
Section: Introductionmentioning
confidence: 99%